EFEITO DO FORTALECIMENTO MUSCULAR INSPIRATÓRIO NA FORÇA MUSCULAR RESPIRATÓRIA, VARIABILIDADE DA FREQUÊNCIA CARDÍACA, PRESSÃO ARTERIAL E QUALIDADE DE VIDA DE MULHERES EM HEMODIÁLISE. - DIAS, Aíla Maria Castro (2017)
Introduction: Chronic Kidney Disease (CKD) is a gradual onset disease in which the individual becomes subject to dialysis, defined by structural abnormalities of the kidneys that can lead to a reduction in renal function, diagnosed by a glomerular filtration of less than 60 ml/min /1.73 m2 for a period of three months or more. Hemodialysis (HD) is the most used treatment, being responsible for extracorporeal blood filtration. In the muscular system, the most affected by muscular atrophy would be the respiratory system. Cardiovascular diseases are the main cause of morbidity and mortality in this population. More than 50% of all deaths occurring in renal patients are due to cardiovascular events. With the dysfunctional autonomic nervous system (ANS), there is a reduction in heart rate variability (HRV) and the development of complex arrhythmias. The multiple limitations and complications of CKD have a negative impact on the quality of life of these patients.Objective: Investigating whether inspiratory muscle training (IMT) in chronic renal patients on hemodialysis can provide additional benefits to the cardiopulmonary system, the autonomic nervous system, and quality of life. Methods: Thirteen women in Hemodialysis Treatment were selected for an inspiratory muscle training program (IMT) with Threshold IMT at 40% of Maximum Inspiratory Pressure (MIP) for 30 daily minutes, during 7 days, for 12 weeks. The maximal MIP and Expiratory Pressure (MEP), blood pressure (BP) before and after each training, Heart Rate Variability (HRV) analysis, pulmonary functional capacity were assessed by the 6-minute walk test (6MWT) and the quality of life by KDQOLSFTM. Results: MIP increased -35.33 ± 20.49 cmH20 to -58.89 ± 23.02 cmH20 (p <0.0028), from MEP 51.67 ± 30 cmH20 to 65.56 ± 20.07 cmH20 (p <0.0281). In the HRV there was no statistically significant improvement. Quality of life improved on Symptoms/ Problems scores at weeks 4, 8 and 12 compared to week 0 (p <0.0009), and on Cognitive Function with improvement at week 12 compared to week 0 (p <0.0491) . The creatinine values presented a statistically significant decrease in the values of weeks 4, 8 and 12 compared to week 0, with p = 0.0004. Conclusion: IMT proved to be an easily applicable alternative treatment for improving respiratory muscle strength and serum creatinine levels, and may be widely used in patients with CKD, concomitant with hemodialysis treatment.